1989
DOI: 10.1093/jn/119.9.1287
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of the Energy Costs Associated with Protein Turnover and Na+,K+-Transport in Growing Lambs

Abstract: A mathematical representation of the energy-requiring processes of protein turnover and Na+,K+-transport in the tissues of growing lambs is described. This model was then used to examine the relative contributions of these processes to ATP expenditure at two different growth rates (90-230 g/d). Protein turnover accounted for 19% of whole-body ATP expenditure at both growth rates examined, with the gastrointestinal tract (GIT), accounting for 25-27%, muscle for 21-26%, skin for 23-26% and liver for 13% of total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
42
0
1

Year Published

1991
1991
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(46 citation statements)
references
References 22 publications
3
42
0
1
Order By: Relevance
“…However, the lower than 100% recovery of energy at levels above maintenance may be because of loss of heat of fermentation or energy retained in the PDV and liver as a result of BW gain. In addition, maintenance energy expenditure and metabolic activity of the gut increase with increasing intake of forages (Gill et al, 1989) because of increased gut tissue mass from fibrous feeds (McLeod and Baldwin, 2000). However, technical limits in the estimation of blood flow and arterial-venous differences or lack of data for unmeasured energy substrates such as nucleic acids and peptides cannot be excluded (Lindsay, 1993).…”
Section: Energy Metabolismmentioning
confidence: 99%
“…However, the lower than 100% recovery of energy at levels above maintenance may be because of loss of heat of fermentation or energy retained in the PDV and liver as a result of BW gain. In addition, maintenance energy expenditure and metabolic activity of the gut increase with increasing intake of forages (Gill et al, 1989) because of increased gut tissue mass from fibrous feeds (McLeod and Baldwin, 2000). However, technical limits in the estimation of blood flow and arterial-venous differences or lack of data for unmeasured energy substrates such as nucleic acids and peptides cannot be excluded (Lindsay, 1993).…”
Section: Energy Metabolismmentioning
confidence: 99%
“…The immune system is an integral part of the GIT (Goddeeris et al 2002) and the majority of the immune cells in the whole body are located in the GIT. Energy costs involved in the immune response of the GIT may therefore be quantitatively far more important than that of the remainder of the body.…”
Section: Immune Cells and Immune Responsementioning
confidence: 99%
“…In agreement with our observations, McLeod and Baldwin (2000) suggested that level of dietary roughage affects ruminal growth via changes in cellular hyperplasia (i.e., cell number). Goodlad (1981) reported that cell proliferation in ruminal epithelium was stimulated when changing the diet of the sheep from roughage to concentrate. Gaebel et al (1987) observed that the number of cell layers of the epithelium increased when changing the diet from 100% hay to 36% hay, was maintained or decreased when changing the diet from 36% hay to 10% hay, with the alterations being fully reversible.…”
Section: Discussionmentioning
confidence: 99%
“…Energy costs can be studied on whole body, tissue, cellular, or molecular levels. Cellular energy-consuming events such as ion transport, protein turnover, and cell proliferation are thought to be important in regulating energy metabolism in tissues (Milligan and Summers 1986;Gill et al 1989;McBride and Kelly 1990). These events represent basal metabolic rate and thermoregulatory functions at the cellular and molecular levels.…”
mentioning
confidence: 99%